OC-032 Surveillance Leads To Improved Outcomes For Patients With Hepatocellular Carcinoma (hcc). (9th June 2014) - Cross, TJS; Ding, W; Richardson, PD; Yousef, F; Palmer, D; Joekes, E; Farrell, C; Evans, J
Abstract : Introduction: 6-monthly ultrasound surveillance is recommended in cirrhotic patients at risk of HCC. The benefit of surveillance has never been demonstrated in a western population. Methods: A retrospective, single centre cohort analysis in patients diagnosed with HCC from 2008–2013. From 2008 an automated recall system for 6-monthly ultrasound was instigated by the radiology department, in preference ad hoc ultrasound requests. Patients with abnormal lesions proceeded to CT, MRI or liver biopsy according to defined international criteria. The primary end-points evaluated were stage of cancer detection (early i.e. BCLC 0 or A), versus late presentation (BCLC B-D) and patient survival from time of diagnosis to 12 months and 60 months. Results: 160 patients were identified. Surveillance status was known in 132 patients. Median patient age was 68 years (57–75), median number of lesions was one, diameter of largest lesion 30 mm (19–50), and AFP 19.5 (5–250). Patients under surveillance were more likely to have disease at a curative stage 67 vs. 39% (p = 0.006, OR 0.59 (0.41–0.84), and had better survival at 1 year 80 vs. 62% (p = 0.04, OR 0.77 (0.62–0.97), and at 5 years 60 vs. 41% (p = 0.046, OR 0.69 (0.48–0.98). On univariate analysis the following variables on survival were evaluated: Age (p = 0.11), Number HCC nodules (p = 0.31), Total diameter of lesions (p = 0.001), Diameter of largest lesion (p < 0.001), AFP (p < 0.001). The presence on imaging of extra-hepatic metastases (p = 0.006), lymph nodes (p = 0.004), and portal vein thrombosis p < 0.001), were associated with poorer survival. Conclusion: Surveillance for hepatocellular carcinoma leads to earlier diagnosis and improved survival. Disclosure of Interest: None Declared.